Penerapan Auricular Acupressure Untuk Mengurangi Konstipasi Pasien Kemoterapi - Edianto Edianto; Agung Waluyo; Sri Yona; Yunisar Gultom (Poltekkes Kemenkes Jakarta III, 2020)
Most cancer patients receive chemotherapy which contributes to prolong life, with the most common side effects of constipation. Constipation causes general symptoms that are bad and affect the quality of life of patients. The purpose of evidance based nursing (EBN) is to identify the effectiveness of Auricular acupressure in overcoming symptoms of constipation in cancer patients receiving chemotherapy. This EBN uses quasi experiments involving 14 participants in the chemotherapy treatment room with pre and post intervention assessments. The results of the analysis of the independent t-test showed that there was a significant difference in the form of faeces on day 6 with p <0.000 (95% CI). Conclusion: Auricular acupressure can be used as a constipation management nursing intervention in cancer patients undergoing chemotherapy.